The ‘Matthew effect’ in Chinese kindergarten principals’ professional development: a mixed-methods study - Qian, Yu; Zhangchen, Shiyuan; Li, Hui (Frontiers in Psychology, 2023)
Principals play a leading role in kindergarten quality improvement, and thus their needs for professional development (PD) should be understood and met. This national study adopted a mixed-methods approach to survey 3,065 kindergarten principals in China and interviewed 16 of them. First, the latent profile analysis of survey data yielded three profiles of PD needs: (1) low (7.5%), (2) medium (22.2%), and (3) high profiles (70.3%), indicating 70.3% of Chinese principals need PD badly. The high-profile group features ‘inexperienced principals working at newly established private kindergartens’, the most disadvantaged among the three groups. Second, ANOVA tests revealed significant rural–urban and public-private differences in Chinese principals’ professional backgrounds and PD needs. In particular, significant public-private and rural–urban differences were observed in the principals’ ‘current degree’ (Fs > 63, ps < 0.001) and ‘desired degree’ (Fs > 39, ps < 0.001). The rural principals aspired more than their urban counterparts to obtain ‘a higher degree” or ‘a certificate’ (ps < 0.05). Third, the follow-up interviews confirmed remarkable rural–urban and public-private gaps in PD needs, indicating a noticeable ‘Matthew effect’: the poor got less, whereas the rich got more. The implications for future PD policy and program development are discussed.